Interview with Milton Santos (Geografares, 2025)
Interview conducted with Professor and geographer Milton Santos on March 14, 2000, by Paulo Cesar Scarim, as part of a master’s thesis defended at the University of São Paulo (USP) in 2000, under the supervision of Professor Ana Fani Alessandri Carlos.